Examining the nexus of infrastructure development and economic growth: Evidence from SAARC countries - Vinay Khandelwal; Varun Chotia; Prashant Sharma; Swati Soni; Sushil Kalyani (Problems and Perspectives in Management)
This study investigates the interconnected roles of infrastructure development, financial growth, and economic growth in SAARC nations. Using principal component analysis, the paper develops a composite infrastructure development index, which integrates factors such as access to electricity, telecommunications, air transport, and agricultural land use. This index serves as a comprehensive measure to assess and compare infrastructural progress across the region. Econometric analyses, including Pedroni’s and Kao’s cointegration tests, reveal long-term associations between the studied variables. The results demonstrate a bidirectional relationship between trade openness and GDP growth in the short term, as well as unidirectional influences from inflation to financial development and from infrastructure development to inflation. However, findings vary across SAARC countries, reflecting their diverse economic structures and development stages. Notably, Afghanistan is excluded due to data limitations, emphasizing the region-specific focus of the results. The study highlights the critical role of targeted infrastructure investment and financial sector reforms in fostering sustainable economic growth. Policymakers are encouraged to consider these findings when designing synchronized public and private sector initiatives to bridge development gaps. By offering detailed insights into region-specific dynamics, this study enriches understanding of the complex interplay between infrastructure, finance, and economic growth in emerging economies.